2023
DOI: 10.1039/d2sc05051j
|View full text |Cite|
|
Sign up to set email alerts
|

Bond breaking of furan–maleimide adducts via a diradical sequential mechanism under an external mechanical force

Abstract: Substituted furan-maleimide Diels-Alder adducts are bound by dynamical covalent bonds that make them particularly attractive mechanophores. Thermally activated [4+2] retro Diels-Alder (DA) reactions predominantly proceed via a concerted mechanism...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 86 publications
0
4
0
Order By: Relevance
“…The elongation profile of this model (Figure a), obtained from CoGEF calculations (DFT ωB97X-D/6-31G*), reveals that the initial scission of C–C bond a (iii, Figure a,b), connecting the ester to the rest of the adduct ( F max = 4.9 nN), is quickly followed by the collapse of the resulting intermediate (iv, Figure a,b), which releases a molecule of furan and regenerates the terminal acrylate and benzylic azide groups (Figure e). The CoGEF calculation suggests a sequential polar mechanism for this process (see SI Section 9.2), and such a mechanism has been previously hypothesized for similar retrocycloadditions. , However, as the CoGEF method does not account for dynamic or thermal effects, which can play a significant role in the dissociation and selectivity mechanisms of mechanophores, , a different mechanism cannot be excluded. Indeed, even though bond a is predicted to cleave preferentially, the elongation of bond c is substantial at E max (Figure a–c), which explains the formation of endo -oxanorbornene as a minor product.…”
mentioning
confidence: 67%
See 1 more Smart Citation
“…The elongation profile of this model (Figure a), obtained from CoGEF calculations (DFT ωB97X-D/6-31G*), reveals that the initial scission of C–C bond a (iii, Figure a,b), connecting the ester to the rest of the adduct ( F max = 4.9 nN), is quickly followed by the collapse of the resulting intermediate (iv, Figure a,b), which releases a molecule of furan and regenerates the terminal acrylate and benzylic azide groups (Figure e). The CoGEF calculation suggests a sequential polar mechanism for this process (see SI Section 9.2), and such a mechanism has been previously hypothesized for similar retrocycloadditions. , However, as the CoGEF method does not account for dynamic or thermal effects, which can play a significant role in the dissociation and selectivity mechanisms of mechanophores, , a different mechanism cannot be excluded. Indeed, even though bond a is predicted to cleave preferentially, the elongation of bond c is substantial at E max (Figure a–c), which explains the formation of endo -oxanorbornene as a minor product.…”
mentioning
confidence: 67%
“…The CoGEF calculation suggests a sequential polar mechanism for this process (see SI Section 9.2 ), and such a mechanism has been previously hypothesized for similar retrocycloadditions. 30 , 31 However, as the CoGEF method does not account for dynamic or thermal effects, which can play a significant role in the dissociation and selectivity mechanisms of mechanophores, 20 , 32 35 a different mechanism cannot be excluded. Indeed, even though bond a is predicted to cleave preferentially, the elongation of bond c is substantial at E max ( Figure 3 a–c), which explains the formation of endo -oxanorbornene as a minor product.…”
mentioning
confidence: 99%
“…54 To our understanding, the shear force generated during injection at 25 ºC acts as a force-actuator mimicking elevated temperature resulting in mechanochemical decoupling of the cycloadduct. [55][56][57][58] Furthermore, these hydrogels were injectable at least up to 48 hours after mixing of the precursors when stored at room temperature (Figure 2B, 2C).…”
Section: S4 B and C)mentioning
confidence: 95%
“…56 In a recent study, researchers have demonstrated that such cyclo-reversion under tension may follow a pericyclic or a non-pericyclic pathway depending on the amount of applied force. 55 Nonetheless, such cyclo-reversion induced by shear-stress has not been observed so far in ECM-polymer derived hydrogel. Plausible chemical structures involved in this process are depicted in Figure 3J.…”
Section: Autonomous Self-healing After Extrusionmentioning
confidence: 97%